Antibiotic resistance rates in Enterococcus spp. in Turkey; a meta-analysis research - (:unkn) unknown (BAYRAKOL MEDICAL PUBLISHER, 2020)
Aim: Inappropriate use of antibiotics cause resistance to vancomycin (VAN) and other antibiotics, and infections with resistant enterococci have high mortality. The aim of this study is to reveal the resistance rate of enterococci in Turkey to VAN and the other antibiotics at antibiotic stewardship program by meta-analysis of the studies from various regions in Turkey. Material and Methods: The clinical enterococci isolates from Turkey between 2007-2016 were evaluated according to inclusion criteria based on the PRISMA. Results: Totally, 37 different data series of 33 articles were included in the study. Data between 2007 and 2016 were divided into two groups as Group-1; 2007-2011 and Group-2; 2012-2016. The differences in antibiotic resistance rates between Group-1 and Group-2 were analyzed. The pooled analysis of 9208 enterococci isolates revealed that the overall VAN resistance rate in enterococci in Turkey is 4.374%. The heterogeneity analysis of the study was determined as Cochrane-Q test (457.6370), I-2=91.91 and p<0.0001. When the group 1 (2007-2011) and group 2 (2012-2016) were analyzed separately, VRE rate between 2012 and 2016 was detected significantly higher than between 2007 and 2011 (6.531%, p<0.001 and 3.393%, p <0.000, respectively). Linezolid (LNZ) resistance rate was found as 0.835% in the 4478 enterococci isolates analyzed at the study. There was more than 3 fold increase (0.578%, to 1.846%) in LNZ resistance in Group-2-period. Discussion: VRE rate in Turkey is still lower than the World's average, while it is close to the rates in European countries. In Turkey, there is a significant increase in resistance rates in enterococci to almost all the antibiotics.
Keywords: Antibiotic resistance; Enterococci; Meta-Analysis; Turkey; ANTIMICROBIAL RESISTANCE; VIRULENCE FACTORS; INFECTIONS; SUSCEPTIBILITIES; MECHANISMS